SISTEM PENGECORAN LOGAM BERTEKANAN (PRESSURE DIE CASTING) UNTUK INDUSTRI KECIL MENENGAH KOMPONEN OTOMOTIF - , M. BURHAN YASIN, Dr. Suyitno, S.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objectives of this research are to design, making and testing the die casting machine to determine the optimal process parameters and to know the performance of the die casting machine. Die casting method was cast metal by injecting molten metal into molds to the pressure. Based on the planning, the total dimensions of machine 2304 x 332 x 447 mm with 2 hydraulic cylinders which each step length of 390 mm and 400 mm. The research method from die casting machine starts by using the aluminum melting furnace separate from the die casting machine up to 700-850oC temperature and heating the mold until the temperature 250-350oC, and then the liquid metal poured into the die casting machine using a ladle through a cylinder injection. After molten metal in the injection cylinder, hydraulic plunger would press it into the mold cavity, injection pressure was maintained during the freezing process. Later, when the casting product was ,freezing, casting mold was opened and the object would be automatically exit the ejector mechanism. The result test from die casting machine casting show that a good product on the parameters: 1. molding temperature of 300oC, melting temperature of 700oC, pressure of 50 kg/cm2, 2. Molding temperature of 350oC, melting temperature of 750oC, pressure of 75 kg/cm2. The materials of this research is using car wheel with the content of Al: 91.43% and Si: 7.79%. Beginning the process required for melting aluminum to a temperature of Â± 700oC is 30 minutes, spraying the die coat is 5 seconds, the process of injection is 8 seconds, the solidification process is 60 seconds and release product from the mold is 2 seconds. So the time required for the initial process is 31 minutes 15 seconds, while for the next process only takes 75 seconds.